Chromatin State-Based Analysis of Epigenetic H3K4me3 Marks of Arabidopsis in Response to Dark Stress - Yan, Hengyu; Liu, Yue; Zhang, Kang; Song, James; Xu, Wenying; Su, Zhen (Frontiers in Genetics, 2019)
Light is essential to plant growth and development. Extended darkness causes dramatic gene expression changes, leading to leaf senescence, hypocotyl growth, petiole elongation, reduced leaf area, and early flowering. However, the underlying mechanism of response to darkness at epigenetic levels remains largely unknown. In this study, we conducted ChIP-seq to generate global epigenomic profiles of H3K4me3 under 3-day extended darkness and normal light conditions in Arabidopsis. We applied chromatin state analysis together with self-organization mapping (SOM) to study the combination of epigenetic regulation under dark stress. The SOM map clusters the segments on the genome according to multiple diverse epigenomic datasets, which breaks the limit of dispersed distribution of epigenetic marks on the genome. Through SOM analysis, we also found that the signals of H3K4me3 were mainly increased after darkness. Analysis of H3K4me3-changed genes together with differentially expressed genes indicated that the genes showing dark-increased H3K4me3 were most involved in senescence and autophagy, and cross-talk existed between dark-induced and natural senescence. In summary, we studied the regulation of the epigenetic H3K4me3 marks of Arabidopsis in response to dark stress using chromatin state and SOM analyses. Our study revealed the regulatory mechanisms of the epigenome in response to dark stress, and SOM analysis based on chromatin states used in our study will also be helpful for other studies on dynamic changes of multiple epigenetic marks.